FRI0126 Corticosteroid therapy-induced injury in patients with systemic lupus erythematosus. (1st June 2001) - Koni, I; Kawano, M; Kitajima, S; Mutoh, H; Katano, K; Inoue, R; Mabuchi, H
Abstract : Background: Corticosteroid therapy is dramatically effective in patients with systemic lupus erythematosus (SLE). Long-term steroid therapy, however, is associated with numerous well-known adverse effects such as vascular disease, osteoporosis and avascular bone necrosis. Objectives: To evaluate the association between steroid therapy and its side effects in patients with SLE. Methods: The medical records of 40 patients with SLE, who have been receiving long term follow up in our clinic from 1970 to 2000, were checked with regard to events possibly related to steroid therapy. The risk of complications associated with the cumulative prednisone dose (CPD) and maximal prednisone dosse (MPD: high >60 mg/day, 60 mg/day > = moderate >30 mg/day, low < = 30 mg/day) was estimated using multivariate logistic analysis, adjusted for age and sex. In CPD 10 mg of prednisone daily for 10 years (36.5 g) was assessed as a reference unit. Results: Five patients had coronary artery disease and 2 of them died. Hypertension was found in 16 patients, stroke in 5, diabetes mellitus in 13, osteoporosis in 20, avascular bone necrosis in 7 and herpes zoster in 11. There were statistically significant relationships between CPD and osteoporosis (RR 8.5, p < 0.01), and coronary artery disease (RR 3.7, p < 0.05). The development of stroke also has a tendency related to CPD, whereas herpes zoster and avascular bone necrosis were associated with MPD (RR 5.1, p < 0.05 and RR 5.2, p = 0.1). Moreover hypertension and diabetes mellitus were more related to age and body mass index, respectively. Conclusion: In SLE patients long-term corticosteroid therapy frequently induced some adverse effects, which could be identified as two distinct types: one is cumulative dose-related injury like osteoporosis and another is maximal dose-related injury like herpes zoster. Steroid-sparing strategy could be needed in order to minimise cumulative and high-dose corticosteroid exposure.